Development of PID control parameters in proportional valves for a wastewater treatment plant filtration process - Quispe Quispe, Jhon Eloy (2022)
Wastewater treatment has remained a topic of interest over the years, since this method allows the water to be reused in other activities, since it establishes a process of conversion to "clean water"; however, this water must comply with quality standards that support the healthiness of the water. On the other hand, the treatment systems are still managed through manual processes, in which the variables and parameters of the plant are measured, however, these do not tend to be accurate, which leads to overflows within the system and consequently contaminate the quality of the water. Therefore, the present study aims to analyze the PID control parameters in proportional valves for a wastewater treatment plant filtration process. Also, it was essential to establish a flow chart of plant processes, and then implement sensors and actuators in the filtration process, in turn, equations were established to find the gain, where a ki=0.5359 and kd=5.1042 were achieved. Therefore, constant oscillations were obtained as a result within the level control, by means of the SCADA system. Finally, it was concluded that the implementation of a PID control system minimized the oscillations (disturbances) of the system, which generated greater precision of the variables that established the filtering of the process and reduced the water overflow, thus maintaining the healthiness of the process.